2014
DOI: 10.1007/s00256-014-1978-3
|View full text |Cite
|
Sign up to set email alerts
|

Trunnionosis: the latest culprit in adverse reactions to metal debris following hip arthroplasty

Abstract: The imaging findings of periprosthetic soft tissue lesions (pseudotumours) have been typically defined in the context of newer second-generation metal-on-metal hip arthroplasty. More recently, similar findings have been described in the setting of non-metal-on-metal prostheses. Although uncommon, wear and corrosion between the metal surfaces at the head-neck ('trunnionosis') and neck-stem interfaces are the potential culprits. With modular junctions containing at least one cobalt chromium component frequently … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
18
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(18 citation statements)
references
References 33 publications
0
18
0
Order By: Relevance
“…Taper corrosion has been shown to manifest clinically as adverse local tissue reactions as shown in previous literature [2][3][4][5][6][7][8][9][10]. In Cooper's series [25], one patient suffered from moderate abductor necrosis due to pseudotumor formation and subsequent dislocations despite an initial revision surgery, requiring a second revision to change to a constrained liner.…”
Section: Discussionmentioning
confidence: 84%
See 1 more Smart Citation
“…Taper corrosion has been shown to manifest clinically as adverse local tissue reactions as shown in previous literature [2][3][4][5][6][7][8][9][10]. In Cooper's series [25], one patient suffered from moderate abductor necrosis due to pseudotumor formation and subsequent dislocations despite an initial revision surgery, requiring a second revision to change to a constrained liner.…”
Section: Discussionmentioning
confidence: 84%
“…Taper corrosion in modular total hip arthroplasty has recently been recognized to be an important issue, with multiple reports of adverse local tissue reactions even in patients with metal-on-polyethylene arthroplasty [2][3][4][5][6][7][8][9][10]. Cooper et al [3] reviewed ten revised metal-onpolyethylene THA that had elevated serum cobalt and chromium levels, and found visible corrosion at the head-neck junction associated with tissue necrosis and lymphocytic infiltration.…”
mentioning
confidence: 99%
“…A recently proposed theory is that trunnionosis, defined as metal wear at the head-neck junction of a total hip implant, is an important contributor (along with wear at the bearing surfaces) to metal particle release in metal-on-metal total hip arthroplasty [ 14 , 15 ]. Trunnionosis is a recognised issue with implants employing a modular design, which are often used to improve prosthetic flexibility when attempting to restore normal hip biomechanics.…”
Section: What Are the Issues Specific To Metal-on-metal Articulatimentioning
confidence: 99%
“…Some studies have shown that corrosion at the modular interface is capable of generating metal ion levels that supersede that generated at the MoM articular interface [11]. Although many patients who have received such implants have experienced adverse local tissue reaction (ALTR) secondary to corrosion debris generated at the neck-stem junction [12], [13], [14], [15], [16], [17], ALTR has also been observed in the absence of metallosis [18]. Fretting and corrosion can result in the generation of soluble debris that can migrate locally or systemically and contribute to periprosthetic osteolysis, ALTR, neck fracture, or implant failure [8], [19], [20].…”
Section: Discussionmentioning
confidence: 99%